Locating the Global: Schooling in an Interconnected World. Issue 3 (March 2018) - Hull, Glynda A.; Hellmich, Emily A.
Background: Educators in the United States and internationally have become increasingly interested in incorporating international perspectives into curricula, programs, and policy. Rooted in a long history of international education, these efforts have been described variously as "multicultural, " "democratic, " and "international." In this article and our work, we use the term global education for this phenomenon in order to signal, along with others, an important shift in conceptualizing how to prepare students for a globalized world. Objective: This article is an initial exploration of current global education efforts in the United States and internationally. The study asks, "How do schools instantiate the global?" and considers how particular schools incorporated global concerns into their mission, curriculum, pedagogy, and structure. Research Design: The research design consisted of a qualitative case study of thirteen schools located in the United States and Asia. Data Collection and Analysis: Data consisted of online document collection, semi-structured interviews with administrators, teachers, and students, and observations. Data analysis consisted of iterative rounds of open-ended as well as thematic coding. Findings: Findings revealed seven strategies used by schools to integrate a global orientation. Two detailed case studies showcased the complexities inherent in implementing these strategies. Conclusions: This article underscores the challenges that schools in the United States and internationally face in instantiating a global education, particularly the meaningful integration of technology, second/foreign languages, and service learning as well as making a global education available across socioeconomic groups. It calls for additional research on how to foster global orientations that position all young people to become cosmopolitan members of local, national, and worldwide communities.